Pathologizing Latinas: Racialized Girlhood, Behavioral Diagnosis, and California's Foster Care System. Issue 3 (1st December 2019) - Restrepo, Isabella C.
Abstract : Scholars of the welfare system have explored the racialized criminalization of mothers of color who are punished by the foster care system, through control of their children, when they are unable to meet the ideals of middle-class motherhood but have yet to fully articulate a language to understand the ways in which this criminalization and punishment extends to youth once they are placed in the foster care system. Using ethnographic interviews with agents of the care system, I explore the ways in which the system pathologizes Latinas' quotidian acts of resistance and survival like their use of silences through the behavioral diagnosis of Oppositional Defiant Disorder (ODD). I argue that California's foster care system is an arm of the transcarceral continuum, marking girls of color and their strategies of resistance as pathological, thereby criminalizing them through the diagnosis of behavioral disorders.